2016
DOI: 10.1038/srep33709
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rd attenuates breast cancer metastasis implicating derepressing microRNA-18a-regulated Smad2 expression

Abstract: Metastasis remains a major cause of mortality and poor prognosis in breast cancer patients. Anti-metastatic therapies are in great need to achieve optimal clinical outcome in breast cancer patients. Panax Notoginseng Saponins (PNS) has previously been shown to inhibit breast cancer metastasis in mouse. Here the potential anti-metastatic effect of one of the chemical compounds of PNS, ginsenoside Rd (Rd), was further evaluated in mouse mammary carcinoma 4T1 cells. The results revealed that Rd treatment dose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 43 publications
(43 reference statements)
1
43
0
Order By: Relevance
“…In addition, the antimetastatic effects of ginsenoside Rd in liver cancer via blocking the MAPK signaling pathway and inducing focal adhesion formation have been indicated . In addition, ginsenoside Rd also counteracts miR‐18a and mediates the downregulation of Smad2 expression, leading to the suppression of breast cancer metastasis . In the present study, we demonstrated that ginsenoside Rd inhibited migration and invasion of CRC cells in a dose‐dependent manner.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, the antimetastatic effects of ginsenoside Rd in liver cancer via blocking the MAPK signaling pathway and inducing focal adhesion formation have been indicated . In addition, ginsenoside Rd also counteracts miR‐18a and mediates the downregulation of Smad2 expression, leading to the suppression of breast cancer metastasis . In the present study, we demonstrated that ginsenoside Rd inhibited migration and invasion of CRC cells in a dose‐dependent manner.…”
Section: Discussionsupporting
confidence: 58%
“…Hou et al, 2017;Yan et al, 2017;Wang et al, 2016;Xie et al, 2016 20(S)-PPT Re (2S,3R,4R,5R,6S)-2-[(2R,3R,4S,5S,6R)-2-[[(3S,5R,6S,8R,9R,10R,12R,13R,14R,17S)-3,12-dihydroxy-4,4,8,10,14-pentamethyl-17-[(2S)-6-methyl-2-[(2S,3R,4S,5S,6R)-3,4,5-trihydroxy-6-(hydroxymethyl) oxan-2-yl]oxyhept-5-en-2-yl]-2,…”
mentioning
confidence: 99%
“…In addition, ginsenoside Rd (Rd), one of the chemical compounds in Panax Notoginseng Saponins, has been investigated for its anti-metastatic property recently. The results showed that Rd treatment inhibited the migratory and invasive ability of breast cancer both in vitro and in vivo via suppressing miR-18a-mediated Smad2 expression [96].…”
Section: Regulation Of Mirna-mediated Gene Expressionmentioning
confidence: 98%